L’apport Des Marchés De Capitaux Au Financement Des PME Marocaines - M. Mohamed Oudgou; M. Mohamed Zeamari (European Scientific Journal, ESJ, 2018)
Moroccan SMEs do not use generally capital market due to rigidity of the conditions. Moroccan authorities have introduced the measurements to deal with this problem and to encourage SMEs to access in the capital market since 2000. However, these measures were less efficient because they are multiple reason, but indeed, it still attributed to the financial and institutional conditions of access to capital market. The article target is to analyze capital market reforms and its contribution to financing Moroccan SMEs. In order to help us to determine the constraints of access the SMEs to direct finance. In fact, to achieve the target we need to adopt a methodology based on the analysis of secondary statistics and official reports of the main actors of the capital markets in Morocco.